Sabbath Observance in Luke-Acts: Situating the Earliest Followers of Jesus Within Judaism - David Wilber (E-Journal of Religious and Theological Studies)
This study demonstrates that Luke presents the earliest followers of Jesus as steadfast Sabbath observers, challenging the common assumption that they abandoned or disregarded this practice. By closely examining the references to the Sabbath in Luke’s Gospel and Acts, it is observed that Luke consistently depicts Sabbath worship as a standard practice among Jewish and Gentile believers. This portrayal suggests that the earliest followers of Jesus did not believe the Sabbath had been abrogated but saw it as integral to their faith and community life. These findings invite modern Christians to reconsider the relevance of Sabbath observance in their own spiritual lives. By highlighting the continuity between Judaism and the emerging Christian movement, this study contributes to scholarship on early Christian identity and practice, portraying the earliest followers of Jesus as a movement within Judaism.